Parameter estimation techniques for fiber bragg grating sensors - Tang, Yu (2010)
In recent decades, fiber Bragg grating sensors (FBGSs) have been widely implemented for measurements in various dynamic or static fields. The basic properties of the FBGSs are their wavelength-encoded measured information and their inherent self-referencing. When the light delivered from the light source reaches the FBGSs, signal waves that are close to the Bragg wavelength are reflected by the fiber Bragg grating (FBG) and the others waves pass through the FBG. Hence, the value of the Bragg wavelength can be obtained by measuring the reflected waves with an optical spectrum analyzer. Physical properties such as the fiber reflectance index and the Grating pitch will change with strain and temperature, thus causing a shift of the Bragg wavelength. Based on this principle, measuring the shift of the Bragg wavelength provides a means to monitor external strain and temperature variations. However, to produce an accurate result, the ability to detect small measured-induced wavelength shifts is critical.